POLITICAL INVESTMENT AND CLASSIFICATION INFLUENCE OF THE INDUSTRIAL SECTOR IN ECONOMIC VALUE ADDED (EVA) - Mussatto, Alejandro Torres; Mayne, Eric Salinas (European Scientific Journal, ESJ, 2014)
While the financial ratios focus on a relative analysis of various figures in the financial statements, to then analyze them altogether (an individual analysis of ratios provides non-existent information), EVA is aimed to measure and/or evaluate the contributions of money invested by the shareholders in the company. This study determines the existing relationship between EVA of companies in Chile and the economic sector that they represent, as well as the influence that the investment policy has in the creation or destruction of value, all between 2010 and 2013. Companies whose main activity is to cover basic services for the population and companies that administer the resources that will be part of pensions present the best levels of value creation. On the other hand, those companies who are in the industrial, retail or transportation business present value destruction, mainly given by the high capital these types of companies require through an expansive investment policy.